2001
DOI: 10.1046/j.1365-2958.2001.02230.x
|View full text |Cite
|
Sign up to set email alerts
|

ASalmonellainositol polyphosphatase acts in conjunction with other bacterial effectors to promote host cell actin cytoskeleton rearrangements and bacterial internalization

Abstract: A central feature of Salmonella pathogenicity is the bacterium's ability to enter into non‐phagocytic cells. Bacterial internalization is the consequence of cellular responses characterized by Cdc42‐ and Rac‐dependent actin cytoskeleton rearrangements. These responses are triggered by the co‐ordinated function of bacterial proteins delivered into the host cell by a specialized protein secretion system termed type III. We report here that SopB, a Salmonella inositol polyphosphatase delivered to the host cell by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
408
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(433 citation statements)
references
References 40 publications
20
408
2
3
Order By: Relevance
“…Salmonella had been reported to invade nonphagocytic cells by macropinocytosis and SopB is involved in regulating actin dynamics to promote Salmonella-induced invasion (33). Because HeLa cells are nonphagocytic cells, the route of bacteria uptake by HeLa cells in their study could most likely be via macropinocytosis instead of the phagocytic pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Salmonella had been reported to invade nonphagocytic cells by macropinocytosis and SopB is involved in regulating actin dynamics to promote Salmonella-induced invasion (33). Because HeLa cells are nonphagocytic cells, the route of bacteria uptake by HeLa cells in their study could most likely be via macropinocytosis instead of the phagocytic pathway.…”
Section: Discussionmentioning
confidence: 98%
“…SopB/ SigD, another Salmonella virulence factor translocated by the TTSS (Patel & Galán, 2005), has also been proposed to mediate actin cytoskeleton rearrangements and bacterial Abbreviations: DAPI, 4,6-diamidino-2-phenylindole; GAP, GTPaseactivating protein; GEF, GDP-GTP exchange factor; GST, glutathione S-transferase; MAPK, mitogen-activated protein kinase; PtdIns 4,5-P 2 , phosphatidylinositol 4,5-bisphosphate; PtdIns 3,4,5-P 3 , phosphatidylinositol-3,4,5-trisphosphate; TTSS, type III secretion system. entry in a Cdc42-dependent manner (Murli et al, 2001;Zhou et al, 2001). Recently, we have also reported that SigD produces a strong inhibitory effect in yeast (Alemán et al, 2005).…”
Section: Introductionmentioning
confidence: 89%
“…SigD, a Salmonella homologue of IpgD from Shigella (Niebuhr et al, 2000), is an inositol polyphosphate phosphatase, bearing characteristic motifs 1 and 2 of mammalian inositol 4-phosphatases, as well as a putative synaptojanin (inositol 5-phosphatase)-like domain (Hong & Miller, 1998;Norris et al, 1998;Marcus et al, 2001). Although Salmonella cells lacking sigD are still able to invade host cells (Zhou et al, 2001), elimination of phosphatidylinositol 4,5-bisphosphate (PtdIns 4,5-P 2 ) from invaginating regions during phagocytosis induced by the bacteria depends on SigD (Terebiznik et al, 2002). SigD also seems to be important for the generation of the characteristic pools of phosphatidylinositol 3-phosphate in the membrane of the Salmonella-containing vacuole (Hernández et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…SPI-1 is required for invasion during oral infection, and the effectors encoded in this pathogenicity island are involved in cytoskeleton rearrangements of epithelial cells to promote the entry of Salmonella via macropinocytosis [16,17]. SopE/SopE2 and the inositide phosphate phosphatase SopB are some of the effector proteins responsible for the induction of macropinocytosis.…”
Section: Introductionmentioning
confidence: 99%